2009
DOI: 10.2340/16501977-0298
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dependence in daily activities combined with a self-rating of difficulty

Abstract: The combined approach to data collection gave a diversified, information-rich picture. The assessment used is easy to administer and can be used in practice contexts in different countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 23 publications
0
55
0
Order By: Relevance
“…Each assessment was recorded on a three-point scale: independent/partly dependent/dependent. For each item where the participant was rated as independent, he/she was asked to state whether the particular activity was performed with or without difficulty (Iwarsson, Horstmann, & Sonn, 2009). Based on the fact that the majority of the participants were independent in ADL, a dichotomous variable labelled ADL difficulty was constructed, with "no" indicating that the participant performed all 9 activities without difficulty and otherwise "yes".…”
Section: Study Context and Participantsmentioning
confidence: 99%
“…Each assessment was recorded on a three-point scale: independent/partly dependent/dependent. For each item where the participant was rated as independent, he/she was asked to state whether the particular activity was performed with or without difficulty (Iwarsson, Horstmann, & Sonn, 2009). Based on the fact that the majority of the participants were independent in ADL, a dichotomous variable labelled ADL difficulty was constructed, with "no" indicating that the participant performed all 9 activities without difficulty and otherwise "yes".…”
Section: Study Context and Participantsmentioning
confidence: 99%
“…In a recent study, in addition to the main findings concerning the relevance and usefulness of a combined assessment approach to capture ADL ability, 11 we demonstrated surprisingly large differences in ADL dependence among 5 national samples (ie, Sweden, Germany, the United Kingdom, Hungary, and Latvia). The results indicated that reasons other than functional limitations (ie, limitations within the person, also called intrinsic disability) 12 influenced the results.…”
mentioning
confidence: 72%
“…To measure the level of difficulty regarding independent ADL, a study-specific extension [34] of the ADL Staircase [35] was used. First, based on an interview and observation, five personal activities of daily living (P-ADLs: bathing, dressing, going to the toilet, transfer and feeding) and four instrumental activities of daily living (I-ADLs: cleaning, shopping, transportation and cooking) were assessed as: performed independently, partly dependently or dependently.…”
Section: Healthmentioning
confidence: 99%
“…By using a study-specific extension of the ADL Staircase [34], information on independence without difficulty, as well as with difficulty in ADL was captured, resulting in a more detailed picture of ADL performance than is usually provided. Still, differences between users and non-users of ADs regarding more social or leisure activities, such as visiting friends, participating in club activities or going to the cinema or theatre, remain to be ADs.…”
mentioning
confidence: 99%
See 1 more Smart Citation